PEMBUATAN MINUMAN KESEHATAN BERBASIS HERBAL UNTUK WARGA DESA KANDANGAN, KECAMATAN KANDANGAN, KABUPATEN KEDIRI - Tukiran, Tukiran; Suyatno, Suyatno; Hidajati, Nurul; Samik, Samik (Universitas Negeri Surabaya, 2019)
Kandangan Village, is one of the villages in Kandangan sub-district, Kediri where some of its citizens workas farmers, farm laborers, carpenters, masons, construction workers, vegetable vendors, open food stallsand chop. Meanwhile, most of the housewives do not work because they take care of housework. Some ofthem are housemaids, washing and ironing workers, and selling various daily necessities at home(chopping). One type of training from the PKM given was a training in making liquid-based herbal healthdrinks, including syrup empon-empon, minuman alang-alang, and beras kencur which are ready for sale inâ€œcafÃ©â€ and herbal shops. This PKM activity was carried out in August 2018 involving 13 housewives fromKandangan village, which began with the presentation of training materials by the PKM Team, followed byassistance in the practice of making herbal-based health drinks, and ended with reflections/feedback andgiving questionnaires. The target of this PKM activity is the increasing skills of housewives in training inmaking herbal-based health drinks. The results of the questionnaire can be seen that PKM activities aredeclared to have gone well and have been able to provide understanding and strengthening skills in makingherbal-based health drinks for participants.